Composição florística, estrutura e heterogeneidade ambiental da comunidade arbórea de uma várzea em Porto Ferreira, SP, Brasil - Konopczyk, Rafael Marques Guimarães [UNESP] (2014)
Floodplains are extensions of area that border the tracing of medium and large rivers, which are subject to flooding during periods of river discharge. According with degree of flooding, the vegetation tends to have specific floristic and structural characteristics. In the present study, we intended to investigate and characterize the tree community of a lowland forest situated by the river Mogi Guaçu, at the “Parque Estadual de Porto Ferreira”, São Paulo State. This study aimed to examine how the flood pulses influence the composition and organization of the tree community floodplain. For that, was carried out a survey of a vegetation data and of environmental variables with regard of topography, flooding, drainage and physicochemical properties of soil. Thus, was allocated in the area 30 plots of 400 m2 each one distributed along two transects according with environmental conditions. In the plots were measured and identified all trees with a perimeter greater than 10 cm at breast height (1.3 m) and characterized the flooding regime and drainage, the topography and physicochemical properties of soil. For analyzing the phytosociological descriptors were used the absolute and relative value of dominance, density and frequency, the importance value (IV), the diversity index (H’) and the Pielou equability (J’) which were obtained by FITOPAC program. The effect of variables Days of flooding, Average elevation and Elevation range were tested by a linear mode using structural and richness parameters between the plots. Those same variables also were used to generate two groups according to cluster analyses k-means, which were used for an indicator species analyses (ISA). A floristic and structural analysis was carried out in a UPGMA using the Bray-Curtis index. Permutation tests were performed to verify differences between groups with regard soil properties and structural parameters. Were carried out three PERMANOVAS, the first to...